Analisis Hukum Syariah Terhadap Bisnis Fintech Peer-To-Peer Lending doi Indonesia - Silalahi, Bob Ben Salomoan; B, Baidhowi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of financial technology, particularly Peer-to-Peer (P2P) lending services, has brought significant innovation in access to financing in Indonesia. However, conventional P2P lending practices that still use interest-based systems and contain elements of uncertainty (gharar) pose challenges from an Islamic law perspective. This article aims to analyze the application of Islamic economic law principles in the fintech P2P lending business in Indonesia, examine regulations issued by the Financial Services Authority (OJK) and fatwas from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), and evaluate the challenges and opportunities in implementing sharia-compliant fintech P2P lending. The research employs a qualitative approach through literature studies from various primary and secondary sources. The findings indicate that although regulatory frameworks and sharia fatwas exist, gaps remain in operational practices, particularly regarding sharia supervision, transparency, and Islamic financial literacy. Therefore, harmonization of regulations, strengthening of Sharia Supervisory Boards, and enhancement of sharia literacy are necessary for fintech P2P lending to function as a fair, transparent, and Islamically compliant financing instrument.